2005
DOI: 10.1090/s0002-9939-05-08280-8
|View full text |Cite
|
Sign up to set email alerts
|

Random holomorphic iterations and degenerate subdomains of the unit disk

Abstract: Abstract. Given a random sequence of holomorphic maps f 1 , f 2 , f 3 , . . . of the unit disk ∆ to a subdomain X, we consider the compositionsThe sequence {F n } is called the iterated function system coming from the sequence f 1 , f 2 , f 3 , . . . . We prove that a sufficient condition on the domain X for all limit functions of any {F n } to be constant is also necessary. We prove that the condition is a quasiconformal invariant. Finally, we address the question of uniqueness of limit functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…proved the following result. In [4] Keen and Lakic showed that the converse of (ii) also holds, as follows. In higher dimensions the story is different.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…proved the following result. In [4] Keen and Lakic showed that the converse of (ii) also holds, as follows. In higher dimensions the story is different.…”
Section: Introductionmentioning
confidence: 91%
“…In [2] Beardon, Carne, Minda and Ng proved the following result: In [5] Keen and Lakic showed that also the converse of (2) holds:…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The motivation for our study comes from discrete dynamical systems, where one is concerned with the iterates of a map f : X → X. In our more general context, given any collection F of self maps of X, we define a composition sequence generated by F to be a sequence (F n ), where F n = f 1 f 2 · · · f n and f i ∈ F. Composition sequences generated by sets of analytic self maps of complex domains have received much attention; see, for example, [2,6,13,14]. There has been particular focus on generating sets composed of Möbius transformations that map a disc within itself -see [1,4,5,12,15,16] -partly because of applications to the theory of continued fractions.…”
Section: Introductionmentioning
confidence: 99%